Trials of Kate Hope - Downing, Warwick 1931- (Boston : Houghton Mifflin Co., 2008)
At the young age of fourteen, Kate Hope is licensed to practice law in the state of Colorado in 1973, and with the help of her lawyer grandfather, and memories of her dead father, also a lawyer, she tries the case of a dog that is slated to be destroyed for attacking a baby.
Accelerated Reader AR